AESTHETICS AND PROFESSIONALISM IN TRANSLATION (Ustozlar uchun, 2025)
This paper explores the interrelationship between aesthetics and professionalism in translation, focusing on how these two components contribute to translation quality. Aesthetics reflects the stylistic beauty, emotional resonance, imagery, and poetic nuances of the source text, while professionalism encompasses linguistic competence, ethical responsibility, methodological precision, and cultural awareness. The research draws upon the theories of leading international scholars such as Roman Jakobson, Eugene Nida, J. C. Catford, Susan Bassnett, Lawrence Venuti, Juliane House, Hans J. Vermeer and Christiane Nord. Their theoretical contributions illuminate the balance between stylistic artistry and professional discipline.Additionally, the works of Uzbek scholars — Shavkat Rahmatullayev, Abduaziz Abduazizov, and G’afur G’ulom — demonstrate how national translation traditions integrate aesthetics and professionalism in rendering Uzbek and world classics. The study concludes that aesthetics and professionalism are not opposing forces but complementary dimensions of successful translation.